Faham Kebendaan: Pandangan Kritis Abu Al-Hasan 'Ali Al-Nadwi - Ab Majid, Mohamad Kamil (Jurnal Usuluddin, 2000)
Abu al-Hasan 'Ali al-Nadwi is one of the great contemporary Muslim thinker who criticized Western civilization. This article tries to review his perception and opinion about Western's materialism and how he interpret it as a "Dajjal" as mentioned in the tradition of the Prophet s.a.w.